Dominantly inherited diabetes mellitus caused by GATA6 haploinsufficiency: variable intrafamilial presentation. Issue 10 (7th September 2012) - Yorifuji, Tohru; Kawakita, Rie; Hosokawa, Yuki; Fujimaru, Rika; Yamaguchi, Emi; Tamagawa, Nobuyoshi
Abstract : GATA6 haploinsufficiency has recently been reported as the most frequent cause of neonatal diabetes with pancreatic agenesis. Although all previously reported cases represented a de novo mutation with complete agenesis or pronounced hypoplasia of the pancreas, in this study we identified a family with a dominantly inherited mutation. Unlike previously reported cases, the degree of pancreatic hypoplasia and the severity of diabetes varied among members of the family, ranging from neonatally lethal diabetes with only a remnant of pancreatic tissue to adult-onset diabetes associated with dorsal agenesis of the pancreas. These observations further broaden the clinical spectrum of diabetes associated with GATA6 haploinsufficiency.